Climbing behavior and growth response of Mansoa alliacea to various support forms in vertical greening - Jiang, Piao; Zhu, Jinxin; Weng, Shufei; Li, Zhuoran; Xu, Feican (Frontiers in Plant Science, 2025)
IntroductionWith rapidly expanding urban environments, green space is becoming increasingly limited. Vertical greening serves as a viable solution to this challenge, with climbing plants playing a crucial role in creating functional and aesthetic green structures. However, current research on support structures for lianas remains scarce. This study therefore investigates the impact of various support forms on the growth of Mansoa alliacea, a potential species for vertical greening.MethodsOne-year-old Mansoa alliacea seedlings were exposed to eight types of support systems: bamboo poles and PVC pipes with diameters of 8 mm and 24 mm; and climbing nets made of nylon and hemp with mesh sizes of 5×5 cm and 10×10 cm. This study evaluated the effects of these supports on plant morphology, photosynthetic parameters, and biomass allocation.Results and discussionThe results showed that climbing nets promoted better above-ground growth, measured as number of leaves, leaf area, stem length, and internode length, while poles more effectively enhanced root branching. Various supports forms influenced biomass distribution. Climbing nets tended to allocate more biomass to aboveground parts, while support poles tended to allocate more biomass to underground parts. Bamboo poles (8 mm diameter) and hemp nets (10×10 cm mesh size) were found to be the most effective. These results suggest prioritizing rough climbing nets like hemp nets as structural supports for Mansoa alliacea to promote rapid vertical green landscape formation.